Dermoscopy And Reflectance Confocal Microscopy To Estimate Breslow Index And Mitotic Rate In Primary Melanoma - Zamira Barragan-Estudillo; Johanna Brito; Marion Chavez-Bourgeois; Beatriz Alejo; Llucia Alos; Adriana Patricia García; Susana Puig; Josep Malvehy; Cristina Carrera (Mattioli1885, 2022)
Introduction: Non-invasive imaging techniques offer the possibility to optimize the first approach to melanoma. RCM has a promising role in predicting the main prognostic events in the dermoepidermal and papillary dermis.   Objectives: To identify pre-surgical criteria that can predict the main prognostic features of melanoma.   Methods: A retrospective cohort-study evaluated dermoscopic, confocal and histopathological characteristics of consecutively diagnosed sporadic melanomas. RCM-melanoma patterns classified into 1) dendritic-cell, 2) round-cell, 3) dermal nest and 4) combined type. Acral, facial and mucosal locations were excluded.   Results: 92 primary melanomas were included: 44 male and 48 female (mean age 60.4 years, SD 16.2) with a mean Breslow of 1.43mm (SD 1.6). The most frequent dermoscopic presentation was the multicomponent pattern, the predominant confocal pattern was dendritic-cell type (44.6%). The presence of pigmented network on dermoscopy was related to lower Breslow and mitotic rates (both p=0.002); in contrast to the presence of visible vessels, which was related to higher Breslow and mitotic indexes (both p=0.001). Confocal observation of dermal nests or atypical cells in the papillary dermis was related to a higher mitotic rate (p=0.006 and p=0.03, respectively). Similarly, diffuse inflammatory infiltrates visible in the superficial dermis was associated with higher Breslow (p=0.04) and mitotic index (p=0.04).   Conclusions: Dermoscopic and RCM in vivo findings on primary melanoma correlate with histopathologic Breslow index, mitotic rate and tumor infiltrating lymphocytes. The architecture and cytology of primary melanoma can be estimated by combining dermoscopy and RCM prior to excision.